Efficacy and safety of Chinese herbal medicine to prevent and treat COVID-19 household close contacts in Hong Kong: an open-label, randomized controlled trial - Du, Peipei; Lam, Wai Ching; Leung, Choryin; Li, Huijuan; Lyu, Zipan; Yuen, Chun Sum; Cheung, Chun Hoi; Lam, Tsz Fung; Bian, Zhaoxiang; Zhong, Linda (Frontiers in Immunology, 2024)
To evaluate the efficacy and safety of CHM in the prevention of COVID-19 infection and treatment for COVID-19 related symptoms. Design Prospective open-label randomized controlled trial. Setting Participants' home in Hong Kong. Participants Participants who had household close contact with COVID-19-infected family members.Interventions Close contacts were stratified into 4 groups (cohort A, B, C, D) based on symptoms and infection status and were randomized in 4:1 ratio to receive CHM granules (9g/sachet, two times daily) or blank control for 7 days with 2 weeks of follow-up.The primary outcome measure was the rate of positive nucleic acid tests.Secondary outcomes were the proportion of developed COVID-19 related symptoms and adverse events during the whole 3-week study period. Subgroup analysis was used to evaluate demographic factors associated with positive infection rates.Results A total of 2163 contacts were enrolled and randomly assigned to the CHM group (1720 contacts) and blank control (443 contacts) group. During the 21 days, the rate of PCR-positive cases in cohort A was markedly lower in the CHM group (3.6%) compared to the control group (7.0%) (P=0.036). Overall, the rate of infection in the CHM group was significantly lower than that in the control group (10.69% vs. 6.03%; RR 0.56, 95% CI 0.39-0.82) after 7-day treatment.No serious adverse events were reported during the medication period.The preliminary findings indicate that CHM may be effective and safe in preventing COVID-19. Future double-blind, randomized controlled trials and long-term follow-up are needed to fully evaluate the efficacy of CHM in a larger contact population.